How fault evolution changes strain partitioning and fault slip rates in Southern California: Results from geodynamic modeling. Issue 8 (26th August 2017) - Ye, Jiyang; Liu, Mian
Abstract: In Southern California, the Pacific‐North America relative plate motion is accommodated by the complex southern San Andreas Fault system that includes many young faults (<2 Ma). The initiation of these young faults and their impact on strain partitioning and fault slip rates are important for understanding the evolution of this plate boundary zone and assessing earthquake hazard in Southern California. Using a three‐dimensional viscoelastoplastic finite element model, we have investigated how this plate boundary fault system has evolved to accommodate the relative plate motion in Southern California. Our results show that when the plate boundary faults are not optimally configured to accommodate the relative plate motion, strain is localized in places where new faults would initiate to improve the mechanical efficiency of the fault system. In particular, the Eastern California Shear Zone, the San Jacinto Fault, the Elsinore Fault, and the offshore dextral faults all developed in places of highly localized strain. These younger faults compensate for the reduced fault slip on the San Andreas Fault proper because of the Big Bend, a major restraining bend. The evolution of the fault system changes the apportionment of fault slip rates over time, which may explain some of the slip rate discrepancy between geological and geodetic measurements in Southern California. For the present fault configuration, our model predicts localized strain in western Transverse Ranges and along the dextral faults across the Mojave Desert, where numerous damaging earthquakes occurred in recent years. Key Points: Numerical models show fault initiations and their impact on strain partitioning in Southern California over the past few million years New faults initiate to increase mechanical efficiency of accommodating the relative plate motion Slip rates between faults on the western and eastern sides of the San Andreas plate boundary zone are generally codependent